The Starving Ellipticals of Fossil Groups - Hon, Suei Hei (fi=Turun yliopisto|en=University of Turku|, 2018)
Fossil Groups (FGs) are unique galaxy systems with extensive X-ray halos and large magnitude gaps between members. It has been theorized that they are old and dynamically relaxed systems formed by multiple galaxy mergers. Their similarity to cD galaxies motivates us to investigate the outskirts of their brightest group galaxies (BGG) in search of merger remnants. We extracted the surface brightness profile and the structural information from 15 Fossil Group BGG. No evidence of recent mergers, such as tidal tails and cD halos, was found in the analysis. The ellipticity and isophote shape provide supports for a dry merger model, yet this is not conclusive. The colour gradients of two objects return conflicting results, suggesting FGs might originate from diverse formation scenarios. Overall, the absence of recent mergers is consistent with past findings. We conclude that FGs are systems that have not experienced merger activity for a long period of time, a class of "starving" (or transient) groups waiting for new infalling galaxies.